The role of correcting osteotomy of Calcaneus with bioglassceramic implant in foot deformation treatment on the background of neurological diseases - V.M. Shimon; A.A. Sherehii (Acta Medica Leopoliensia, 2020)
Flat feet is a common pathology, which aggravates the course of several neurological diseases, including cerebral palsy and Spina bifida; at the same time, it is a result of a prolonged imbalance of muscles.